Price Theory - Weyl, E. Glen (Microsoft Research, 2014)
I propose an alternative to the conventional definition of price theory as pricetaking in partial equilibrium. Instead I define it as a methodological approach that derives a small collection of prices sufficient to characterize low-dimensional allocative problems in rich aggregate economies. A classic example is optimal income taxation formulas based on summary elasticities of taxable income and measures of inequality. This definition derives from a tight analogy to thermodynamics in physics and contrasts both with reductionism (e.g. game theory) that seek more complete characterizations of lower-dimensional economies and reduced-form empiricism that builds off of available empirical evidence. I use recent research from fields ranging from market design to international trade to highlight this definition and both the contrasts and complementarities of such price theory with empiricism and reductionism. I then argue that this schema helps make sense of the historical evolution of price theory during the 19th and 20th centuries, especially its interaction with the other traditions during the last half century, when price theory was closely identified with the University of Chicago. I conclude by expositing the analytic tools of price theory.